2015
DOI: 10.5505/tjtes.2015.28227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes with three different intramedullary nailing devices in treatment of unstable trochanteric fractures

Abstract: BACKGROUND:The aim of this study was toreport our experience regarding the use of three different methods for intramedullary nailing in the treatment of intertrochanteric fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 15 publications
5
67
1
2
Order By: Relevance
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
“…These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes. Of these, two studies reported that there was no significant difference in the operative time between the InterTan intramedullary nail (IT) group and the GN or PFNA group [15, 20].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a biomechanical study of hip compression screw with deployable talons, Bramlet and Wheeler [3] reported that talon deployment significantly improved the interfragment torsion and compression strength. Furthermore, Zehir et al [4] reported lower cut-out rates and shorter operative times with talon distal fix/lag screw proximal femoral nail when compared to other proximal femoral nail types.…”
Section: öZmentioning
confidence: 99%
“…All fractures were reduced by closed means. Standard operative techniques, which are recommended by the manufacturer and have been described in detail in instruction manuals or earlier studies [19,20] were used. All patients received a prophylactic dose of an intravenous antibiotic.…”
Section: Methodsmentioning
confidence: 99%